Education, religion, and creativity: essays in honour of Professor Yogendra Singh - Yogendra Singh; Ishwar Modi (ed.) (Jaipur: Rawat Publications, 2013)
Yogendra Singh, b. 1932, Indian sociologist; contributed articles; with reference to India.
Keywords: Religion; Creative Ability; Education; Social Sciences